2018
DOI: 10.1111/ane.12926
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield segmentation in temporal lobe epilepsy: Relation to outcomes

Abstract: ObjectiveTo investigate the clinical and surgical outcome correlates of preoperative hippocampal subfield volumes in patients with refractory temporal lobe epilepsy (TLE) using a new magnetic resonance imaging (MRI) multisequence segmentation technique.MethodsWe recruited 106 patients with TLE and hippocampal sclerosis (HS) who underwent conventional T1‐weighted and T2 short TI inversion recovery MRI. An automated hippocampal segmentation algorithm was used to identify twelve subfields in each hippocampus. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Interestingly, cellular loss in CA3, CA4 and dentate gyrus in patients with mTLE were associated with a decline in declarative memory, but loss of cells in CA1 was not (Coras, Pauli, et al, 2014). Nevertheless, no significant relationship between in vivo MRI‐based hippocampal subfield volumes and clinical variables (i.e., duration and age of onset) have been found (Bower, Kilpatrick, Vogrin, Morris, & Cook, 2000; Kreilkamp, Weber, Elkommos, Richardson, & Keller, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cellular loss in CA3, CA4 and dentate gyrus in patients with mTLE were associated with a decline in declarative memory, but loss of cells in CA1 was not (Coras, Pauli, et al, 2014). Nevertheless, no significant relationship between in vivo MRI‐based hippocampal subfield volumes and clinical variables (i.e., duration and age of onset) have been found (Bower, Kilpatrick, Vogrin, Morris, & Cook, 2000; Kreilkamp, Weber, Elkommos, Richardson, & Keller, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that volume loss in selective hippocampal subfields is correlated to epilepsy. [39][40][41] It has been shown that different parts of the hippocampus show different levels of resistance to disruption in perfusion, with the CA1 region known to be particularly sensitive, whereas CA2 and CA3 are thought to be particularly resistant. 42 Thus, it may be possible that this change in VD is also associated with particular hippocampal subfields.…”
Section: Additional Limitations and Future Directionsmentioning
confidence: 99%
“…The widespread abnormalities observed in this work (Figure ) are concordant with evidence from both histopathology and imaging research indicating abnormalities in the CA1‐CA3 subfields and dentate gyrus, which run most of the length of the hippocampus (eg, Briellmann et al, von Oertzen et al, Stefanits et al); for comparison of the orientations of these subfields to the CSA profiles, please see Figure . Using automated tools for hippocampal subfield segmentation, group‐level differences in these subfields are also observed, but patient‐specific results at 3 or 7 T have so far remained inconclusive as to the use in either improved detection of HS or prediction of postoperative seizure outcome . Even when manual subfield delineation did provide a distinction between HS types 1 and 2, automated subfield volumetry did not …”
Section: Discussionmentioning
confidence: 99%